Clinical studies investigating the role of mesenchymal stem cells in healing of fracture non-unions: a systematic review - Sumaiya Khan; Asif Peracha; Arslan Ahmed Abro; Muhammad Sufyan; Muhammad Kazim Rahim Najjad; Sobia Aziz; Muhammad Mairaj Khan (Journal of the Pakistan Medical Association, 2023)
Objective: To identify and evaluate the effectiveness of mesenchymal stem cells (MSCs) in augmenting healing in fracture non-unions. Methods: A focused literature search was performed on the PubMed/MEDLINE index using the keywords: “non-union”, “mesenchymal stem cells”, “bone healing”, “MSC”, “stem cells”, and their MeSH terms. The search was reiterated until the 10th of August 2022. Clinical studies were included that assessed the effect of MSCs on fracture non-unions. Results: Thirteen human clinical trials, studying a total of 318 participants were identified and studied. MSCs with and without biological or synthetic scaffolds were found to be effective in healing of non-unions. Conclusion: MSCs has been demonstrated to have promising outcomes in the treatment of bone non-union and tissue engineering methods utilizing MSCs may well prove to be valuable in accelerating the process of bone union. However, clinical application of MSCs as a standard method in achieving union in fracture non-unions requires larger clinical trials with a standardised approach to analyzing outcomes. Keywords: Medline, Mesenchymal, Stem Cells, Tissue Engineering, Fractures